2022
DOI: 10.21203/rs.3.rs-2386791/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To bury or not to bury the k-wires after fixation of a pediatric both bone forearm fracture, a randomized controlled trial

Abstract: Objectives The primary objective was to compare refracture incidence of both radius and ulna fracture in two groups treated using intramedullary k-wires where the wires were buried in group I and left exposed in group II. The secondary objective was to compare the final functional outcomes and complications incidence. Methods Between March 2019 and February 2021, 60 pediatric patients presented with unstable radius and ulna fractures amenable to surgical intervention using intramedullary K-wires were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The risk of bias assessment by using the RoB v2 tool revealed that only 1 RCT [ 9 ] had a "low risk" of bias in all five assessment domains. The remaining four RCTs [ 10 , 17 – 19 ] were judged to have “some concern” risk of bias. One RCT [ 18 ] used consecutive non-random sampling for the selection of participants which was deemed an inappropriate method for randomization, but there was no significant difference in the baseline characteristics of participants in the two groups of intervention, suggesting no serious problems during randomization, therefore was judged to have “some concern” risk of bias in the randomization process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias assessment by using the RoB v2 tool revealed that only 1 RCT [ 9 ] had a "low risk" of bias in all five assessment domains. The remaining four RCTs [ 10 , 17 – 19 ] were judged to have “some concern” risk of bias. One RCT [ 18 ] used consecutive non-random sampling for the selection of participants which was deemed an inappropriate method for randomization, but there was no significant difference in the baseline characteristics of participants in the two groups of intervention, suggesting no serious problems during randomization, therefore was judged to have “some concern” risk of bias in the randomization process.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted to compare buried and exposed K-wires in the management of hand and forearm fractures but have yielded inconsistent results due to high risk of infection [ 9 , 10 ]. The gap in existing reviews becomes apparent as these studies do not offer a cohesive and thorough comprehension of the effectiveness and risks associated with exposed versus buried K-wires.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Khaled M et al [10] showed no significant difference in the complication rate, including pin infection incidence between exposed and buried K-wire. Given these inconsistencies, a meta-analysis may help.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have been conducted to compare buried and exposed K-wires in the management of hand and forearm fractures but have yielded inconsistent results. [9,10] A randomized trial study conducted by Maradei-Pereira JAR et al[9] distal radial, fractures showed a greater risk of infection when K-wires were left exposed than when they were buried. On the other hand, Khaled M et al[10] showed no significant difference in the complication rate, including pin infection incidence between exposed and buried K-wire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation